Freud e a memória do futuro (Freud and the memory of the future) - Rozenthal, Eduardo (Estudos da Língua(gem), 2013)
Neste artigo, por um lado, sigo o movimento da teoria freudiana que permite associar-lhe o pensamento da memória do presente, organização significante baseada nas diferenças entre traços mnêmicos. Descrevo, antes, a convergência entre as proposições psicanalíticas e a tradicional memória do passado, que consiste na reprodução passiva do que foi objetivamente percebido. Finalmente, acompanho os enunciados freudianos sobre o primado do afeto, onde a memória do imemorável abre as portas do futuro à subjetividade. Conservando seus efeitos na estruturação simbólica, a compreensão da memória do futuro libera uma descrição mais singularizada do processo de subjetivação em psicanálise. PALAVRAS-CHAVE: Memória. Subjetividade. Subjetivação. Percepção. Representação. ABSTRACT In this article, on the one hand, I follow the movement of Freudian theory in order to understand its association with the thought of the memory of the present, significant organization based on the differences among mnemonic traces. Before that, I indicate the psychoanalytical propositions that merge with the traditional memory of the past, passive model that consists of the reproduction of what was objectively perceived in the past. Finally, I follow Freudian arguments about the primal importance of the affect (force, drive), based on the argument that the memory of the immemorial times opens the doors of the future to subjectivity. Keeping its effects in the subjective symbolic organization, the understanding of the memory of the future frees a more singular description of the process of “subjectivation” in psychoanalysis. KEYWORDS: Memory. Subjectivity. Subjectivation. Perception. Representation.